2013
DOI: 10.1097/nhh.0b013e3182976135
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Nursing

Abstract: Providing spiritual care is an important foundation of nursing and is a requirement mandated by accreditation organizations. Spiritual care is essential in all clinical areas but particularly in home care and hospice. Clinicians may be unable to respond to spiritual needs because of inadequate education or the assumption that spiritual needs should be addressed by clergy, chaplains, or other "spiritual" care providers. In reality, clinicians in the home may be in the best position to offer spiritual support wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Providing examples of successful communication such as this can improve health care professionals’ comfort levels with their own abilities. Nurses whose education programs have taught them how to incorporate spiritual care into practice were more comfortable doing so (Ruder, 2013). However, not all education comes in the classroom; on-the-job experience or vicarious learning from colleagues may also teach health care professionals communication skills, as other research has shown that more career-advanced nurses are better at incorporating spiritual practice into their care (Ronaldson, Hayes, Aggar, Green, & Carey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Providing examples of successful communication such as this can improve health care professionals’ comfort levels with their own abilities. Nurses whose education programs have taught them how to incorporate spiritual care into practice were more comfortable doing so (Ruder, 2013). However, not all education comes in the classroom; on-the-job experience or vicarious learning from colleagues may also teach health care professionals communication skills, as other research has shown that more career-advanced nurses are better at incorporating spiritual practice into their care (Ronaldson, Hayes, Aggar, Green, & Carey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Selain beban kerja, pendidikan yang tidak memadai memberikan kontribusi untuk dukungan yang tidak memadai bagi kebutuhan rohani pasien oleh para perawat (Ruder, 2013). Perawatan spiritual adalah menaruh pehatian relatif terhadap kebutuhan keagamaan dan eksistensial pasien, termasuk pertanyaan dan pengalaman mereka terhadap makna dan tujuan hidupnya (Jokhemsen in van Leeuwen, Tiesinga, Middel, Post, & Jochemsen, 2009).…”
Section: Spirituality and Spiritual Care Rating Scaleunclassified
“…SC is an important element considered by accreditation organizations, and hence, adequate preparation of nursing candidates for providing this care should be an essential component of university curricula. 13 Education in this matter should centre around the primary principles of SC, such as listening, spending time with patients, respecting their privacy and dignity, maintaining religious practices, and delivering care with kindness and concern. 14–16 …”
Section: Introductionmentioning
confidence: 99%